Settlement of piled-raft foundation for 8-storey building on very soft clay - Win, Khaing Zar (2008)

(untitled)
In the last few years the number of piled rafts, especially those with few piles, has increased. It was therefore necessary to develop calculation models with sufficient accuracy and cost efficiency for practical use. It will be shown that finite-element analysis can be used to fulfill these requirements. This research aims to study the behavior of piledraft foundation. Piled-raft foundation is usually designed for buildings to provide adequate load carrying capacity and to limit the overall settlement and hence control differential settlement within tolerable limits. In this study, proposed model of eight-storey reinforced concrete building with piled raft foundation is located Yangon. The proposed model with piled raft foundation is analysed by using STADD Pro software. Firstly, the thickness of raft and soil modulus is estimated. Secondly, the diameter of pile is estimated by Tomlinson’s equation, and the bearing capacity of pile foundation is calculated by using the method modified form from the general bearing capacity equations. The vertical displacement or the vertical settlement of pile is considered by using the theoretical approach and the results obtained from analysing the combined structure. The lateral load resistance and maximum moment resistance of pile is calculated by Brom’s method. The foundation design is considered 30% of mat and 70% of pile. The research is extended to the pile capacity and bearing capacity of subsoil under the raft in order to verify the appropriate parameters for prediction the settlement of piled-raft foundation of eight-storey building.. Foundation analysis will be carried out by using STAAD Foundation software to predict the settlement of this study.